(untitled) (Papeles, 2024)
This work analyzes pensions in Argentina, which provide coverage for the loss of support suffered by the survivors as the result of the death of the breadwinner. In particular, it studies its origin, its purpose, and the modifications that accompanied the public agenda, as sociocultural circumstances varied. In this development, the legislative reforms and their expansion through jurisprudence stand out, in the face of new budgets susceptible to protection. Likewise, the unavoidable review of the assumptions is proposed, which guarantee social coverage against the economic needs generated by the death contingency, in balance with the sustainability of the system and without losing focus on the foundation of this institution.